Additive engineering to improve the efficiency and stability of inverted planar perovskite solar cells. Issue 30 (24th July 2018) - Gao, Chenglin; Dong, Hongzhou; Bao, Xichang; Zhang, Yongchao; Saparbaev, Aziz; Yu, Liyan; Wen, Shuguang; Yang, Renqiang; Dong, Lifeng
Abstract : A formamidine acetate salt additive engineering strategy is developed to fabricate perovskite solar cells with high efficiency and stability. Abstract : Perovskite solar cells (PSCs) have received extensive attention due to their excellent photovoltaic performance. The quality of perovskite films is crucial to device performance, and introducing additives to the precursor solution is an effective way to control the film morphology and to reduce the defect density. In this paper, formamidine acetate salt (FAAc) is introduced into the precursor solution as an effective additive to greatly improve the quality of perovskite films. With the addition of 5 mol% FAAc, the PSCs with a bis(4-phenyl)(2, 4, 6-trimethylphenyl)amine (PTAA) hole extraction layer demonstrate desirable performance in terms of the open-circuit voltage (1.04 V), the short-circuit current density (23.16 mA cm −2 ), the fill factor (close to 80%), the power conversion efficiency (18.90%), negligible hysteresis, and the device stability (up to 80 days). These results will provide a new avenue for fabricating commercial perovskite solar cells.